Pengelolaan Lembaga Keuangan Mikro Di Kabupaten Sumba Timur - Karolina A. Rewa (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2013)
Facts about poverty and unemployment show a great need for financial services among low-income communities. Therefore, it needs savings and loan activities for people with low incomes. Microfinance institutions exist to help the poor and small businesses so that they can help themselves.One of the Micro Finance Institutions (MFIs) that exist in East Sumba is a cooperative (koperasi) made up of different community backgrounds, such as Civil Servants (PNS), Ethnics, farmers, traders, Fishermen, Private Employees and others.This study aims to examine the background of the formation of cooperatives (koperasi) and UBSP, lending process, and strategies to solve the problems of bad debts. This study uses qualitative descriptive method.The results show that:The background of establishing Micro finance isntitution (LKM) in East Sumba is emerging from the community's initiative with originally started with the work of government and NGO programs.Distributing credits / loans were made during the regular meetings held every monthBad creditscan be minimized by always having regular meetings every month and the sanctions that have been agreed.Keywords: Micro Finance Institutions, Credit, Cooperative (koperasi)